2022
DOI: 10.4322/bds.2022.e2809
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sCD14 levels in patients with endodontic pathology requiring root canal treatment

Abstract: Objective: Dental caries is one of the most common microbial diseases. Because of the infectious nature of the disease, the immunologic response by the host plays an essential role in its development. Therefore, the aim of this study was to evaluate the sCD14 levels in patients exhibiting two to three teeth with caries involving pulp along with apical periodontitis requiring root canal treatment. Material and Methods: This study was carried out on 20 participants, of whom 10 were caries-free (Control) and 10 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Later, 14 articles were removed because of non-compliance with PECO. For instance, tissue analysis ( 15 – 18 ), absence of a control group ( 19 22 ), and non-observational studies ( 23 , 24 ), treatment analyses ( 25 , 26 ), microorganism analyses ( 27 ) and lack of information ( 28 ). Therefore, 17 articles remained in the systematic review ( 6 , 29 44 ) distributed across cross-sectional, cohort, and case-control studies, as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Later, 14 articles were removed because of non-compliance with PECO. For instance, tissue analysis ( 15 – 18 ), absence of a control group ( 19 22 ), and non-observational studies ( 23 , 24 ), treatment analyses ( 25 , 26 ), microorganism analyses ( 27 ) and lack of information ( 28 ). Therefore, 17 articles remained in the systematic review ( 6 , 29 44 ) distributed across cross-sectional, cohort, and case-control studies, as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%